Meta-analysis of surgeon-performed central line placement: Real-time ultrasound versus landmark technique. Issue 4 (April 2018) - Gurien, Lori A.; Blakely, Martin L.; Crandall, Marie C.; Schlegel, Cameron; Rettiganti, Mallikarjuna R.; Saylors, Marie E.; France, Daniel J.; Anders, Shilo; Thomas, Sheila L.; Dassinger, Melvin S.
Abstract : BACKGROUND: Major health care agencies recommend real-time ultrasound (RTUS) guidance during insertion of percutaneous central venous catheters (CVC) based on studies in which CVCs were placed by nonsurgeons. We conducted a meta-analysis to compare outcomes for surgeon-performed RTUS-guided CVC insertion versus traditional landmark technique. METHODS: A systematic review of the literature was performed, identifying randomized controlled trials (RCT) and prospective "safety studies" of surgeon-performed CVC insertions comparing landmark to RTUS techniques. Searches were conducted in MEDLINE, Cochrane, and Web of Science, with additional relevant articles identified through examination of the bibliographies and citations of the included studies. Two independent reviewers selected relevant studies that matched inclusion criteria, and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed. A meta-analysis was conducted using random effects models to compare success and complication rates. RESULTS: Three RCTs were identified totaling 456 patients. The RTUS guidance was associated with better first attempt success (odds ratio [OR], 4.7; 95% confidence interval [CI], 1.5–14.7, p = 0.008) and overall success (OR 6.5, 95% CI: 2.7–15.7, p < 0.0001). However, there were no differences in overall complication (OR 1.9 (95% CI, 0.8–4.4, p = 0.14)) or arterial puncture (OR 2.0 (95% CI, 0.7–5.6, p = 0.18) rates between the two methods. CONCLUSION: Despite many studies involving nonsurgeons, there are only three RCTs comparing RTUS versus landmark technique for surgeon-performed CVC placement. The RTUS guidance is associated with better success than landmark technique, but no difference in complication rates. No study evaluated how RTUS was implemented. Larger studies examining RTUS use during surgeon-performed CVC placements are needed. LEVEL OF EVIDENCE: Systematic review and meta-analysis, level III.